When institutional entrepreneurship failed: the case of a responsibility centre in a Portuguese hospital - Major, M.; Conceição, A.; Clegg, S. (Accounting, Auditing and Accountability Journal, 2018)
Purpose: The purpose of this paper is to demonstrate the role of power relations in initiating and blocking accounting change that involves increased “responsibilisation” and “incentivisation”, and to understand how institutional entrepreneurship is steered by power strategies. Design/methodology/approach: An in-depth case study was carried out between 2010 and 2015 in a cardiothoracic surgery service (CSS) where a responsibility centre was introduced. Findings: Introducing a responsibility centre within a CSS led to a change process, despite pressures for stability. The institutionalisation of change was conditioned by entrepreneurship that flowed through three circuits of power. Strategies were adapted according to changes in exogenous environmental contingencies and alterations in the actors’ relationships. Originality/value: The contributions of the paper are several: first, it demonstrates that the existing literature discussing the implementation of responsibility centres cannot be isolated from power issues; second, it expands understanding of the power dynamics and processes of institutional entrepreneurship when implementing accounting change; third, it shows how change introduced by exogenous political economic events structured organisational circuits of power and blocked the introduction of the change initiative.